Characterization of epidermal bladder cells in Chenopodium quinoa. (5th October 2021) - Otterbach, Sophie L.; Khoury, Holly; Rupasinghe, Thusitha; Mendis, Himasha; Kwan, Kim H.; Lui, Veronica; Natera, Siria H. A.; Klaiber, Iris; Allen, Nathaniel M.; Jarvis, David E.; Tester, Mark; Roessner, Ute; et al.
Abstract: Chenopodium quinoa (quinoa) is considered a superfood with its favourable nutrient composition and being gluten free. Quinoa has high tolerance to abiotic stresses, such as salinity, water deficit (drought) and cold. The tolerance mechanisms are yet to be elucidated. Quinoa has epidermal bladder cells (EBCs) that densely cover the shoot surface, particularly the younger parts of the plant. Here, we report on the EBC's primary and secondary metabolomes, as well as the lipidome in control conditions and in response to abiotic stresses. EBCs were isolated from plants after cold, heat, high‐light, water deficit and salt treatments. We used untargeted gas chromatography–mass spectrometry (GC–MS) to analyse metabolites and untargeted and targeted liquid chromatography‐MS (LC–MS) for lipids and secondary metabolite analyses. We identified 64 primary metabolites, including sugars, organic acids and amino acids, 19 secondary metabolites, including phenolic compounds, betanin and saponins and 240 lipids categorized in five groups including glycerolipids and phospholipids. We found only few changes in the metabolic composition of EBCs in response to abiotic stresses; these were metabolites related with heat, cold and high‐light treatments but not salt stress. Na + concentrations were low in EBCs with all treatments and approximately two orders of magnitude lower than K + concentrations. Abstract : Characterizing the changes in primary and secondary metabolites and lipids of epidermal bladder cells (EBCs) from C. quinoa in response to several abiotic stresses, such as heat, cold, salinity, high light and water deficit.